MSME Strategy to Increase Income during the Covid-19 Pandemic - Marlina, Rina; Sunarsih, Uun (Research of Economics and Business, 2023)
The purpose of this study was to determine the impact of Covid19 on sales of Micro Small Medium Enterprises or MSME (Usaha Mikro Kecil Menengah or UMKM) In BKT Duren Sawit and to find out the strategies taken to increase income during the Covid-19 Pandemic. At BKT Duren Sawit, there are four business sectors, namely the culinary sector, the fashion sector, the household consumption sector and the tourism sector. This study uses a qualitative method with a case study approach. Data collection techniques were carried out by means of Observation, Interview and Documentation. This study uses the Miles & Hubermen model analysis method, namely data reduction, data presentation and verification or conclusions. The results showed that all MSME sectors in Duren Sawit BKT experienced a 30-70% decrease in income. The strategy taken to increase the income of MSMEs in the culinary sector is to partner with the Go Food online platform and maintain product quality. MSME in the Fashion Sector use external advertising media (Banners) and WhatsApp social media and implement Product Innovation strategies. MSME in the household consumption sector apply a price strategy and product strategy, the tourism sector applies a sales promotion strategy.